The Role of Physical Fitness on Cardiovascular Responses to Stress - Anthony S. Leicht (Frontiers Research Topics, 2015)
Cardiovascular responses to physical and/ or mental stressors has been a topic of great interest for some time. For example, significant changes of cardiovascular control and reactivity have been highlighted as important mechanisms for the protective effect of exercise as a simple and effective, non medical therapy for many pathologies. However, despite the great number of studies performed to date (e.g. >54,000 entries in Pubmed for "cardiovascular stress"), important questions of the role stress has on cardiovascular function still remain. For instance, What factors account for the different cardiovascular responses between mental and physical stressors? How do these different components of the cardiovascular system interact during stress? Which cardiovascular responses to stress are the most important for identifying normal, depressed, and enhanced cardiovascular function? Can these stress-induced responses assist with patient diagnosis and prognosis? What impact does physical fitness have on the relationship between cardiovascular function and health? The current topic examined our current understanding of cardiovascular responses to stress and the significant role that physical fitness has on these responses for improved function and health. Manuscripts focusing on heart rate variability (HRV), heart rate recovery, and other novel cardiovascular assessments were especially encouraged.